The Existence Of The Parties' Signatures In The Land Sale And Purchase Binding Agreement With Notary Deed Numbering - Restianti, Dini (International Significance of Notary, 2023)
Abstract : A notary is a public official who is authorized by the state to make authentic deeds whose actions must comply with statutory regulations and Article 1868 of the Civil Code. In making the deed, it must be guided by article 38 UUJN and article 1868 of the Civil Code. The aim of this research is firstly, to analyze the existence of the signatures of the parties in the land sale and purchase binding agreement by notarial deed numbering, and secondly, to analyze the legal protection of the notary and the parties after signing the land sale and purchase binding agreement deed but the certificate has not been checked for the deed numbering.The research method used is normative juridical approach with concepts and laws and regulations. The results of the research and discussion show that: First, the existence of the signatures of the parties in the land sale and purchase binding agreement and the numbering of the notarial deed cannot be separated because after the deed of the sale and purchase binding agreement is made and the BPHTB is paid, it must be read by the notary to the applicant and immediately signed by the parties and the notary are simultaneously numbering the deed because it affects the authenticity of a deed, and if this is not done simultaneously then the authentic power of a deed will be degraded. Second, legal protection for the notary and the parties after signing the deed of the agreement binding the sale and purchase of land but the numbering of the certificate has not been checked, for the seller the form of protection is to ask for a down payment associated with the cancellation of the deed if the buyer defaults, while the form of protection for the buyer is the implementation of the achievement and levering if it has been paid off and has absolute power of attorney, this is feared by the seller for breaking his promise, while the form of notary protection is guided by article 66 UUJN.Keywords: Existence, Signature, Deed Numbering